1994
DOI: 10.1901/jaba.1994.27-575
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Influential Dimensions of Reinforcers on Choice in Students With Serious Emotional Disturbance

Abstract: We examined how reinforcer rate, quality, delay, and response effort combined to influence the choices of 6 youths with learning and behavior difficulties, and the viability of an assessment methodology derived from matching theory for determining differential responsiveness to those reinforcer and response dimensions. The students were given two concurrent sets of math problems that were equal on two dimensions but competed on two other dimensions (e.g., one set yielded higher rate and lower quality reinforce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
170
1
3

Year Published

1997
1997
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(187 citation statements)
references
References 10 publications
13
170
1
3
Order By: Relevance
“…Other parameters, such as the amount of work expended per unit of reinforcer (effort), have also been shown to affect choice among concurrently available reinforcers (e.g., Hursh, Raslear, Shurtleff, Buaman, & Simmons, 1988), and results of two recent applied investigations have replicated this finding. Neef, Shade, and Miller (1994) examined the effects of reinforcer rate, quality, delay, and response effort on time allocation across different math tasks presented on concurrent variable-interval schedules to students with emotional disorders, and found that effort affected choice to some degree. Kerwin, Ahearn, Eicher, and Burd (1995) focused more specifically on response effort while treating children who exhibited feeding disorders.…”
Section: Methodsmentioning
confidence: 99%
“…Other parameters, such as the amount of work expended per unit of reinforcer (effort), have also been shown to affect choice among concurrently available reinforcers (e.g., Hursh, Raslear, Shurtleff, Buaman, & Simmons, 1988), and results of two recent applied investigations have replicated this finding. Neef, Shade, and Miller (1994) examined the effects of reinforcer rate, quality, delay, and response effort on time allocation across different math tasks presented on concurrent variable-interval schedules to students with emotional disorders, and found that effort affected choice to some degree. Kerwin, Ahearn, Eicher, and Burd (1995) focused more specifically on response effort while treating children who exhibited feeding disorders.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, these students exhibited a bias for the nickels that could not be explained by rate of reinforcement alone. In a follow-up study, Neef et al (1994) conducted analyses of students' academic response distributions across two stacks of math problems under differing reinforcer dimension comparisons. Dimensions consisted of (a) rate (i.e., the concurrent VI schedule in place for each stack of math problems), (b) quality (i.e., relative preference for reinforcers available for each stack of math problems), (c) delay (i.e., time between point delivery and exchange for backup reinforcer), and (d) effort (i.e., difficulty of the math problems).…”
Section: Figure 3 the Top Panel Depicts Possible Variations In Bias mentioning
confidence: 99%
“…However, if a bias is detected via reinforcer parameter manipulations, the practitioner can isolate the preferred dimension and program reinforcers accordingly; this approach may be useful in contexts that prohibit the ability to arrange all appetitive dimensions of reinforcement (e.g., specific classroom demands associated with the target response do not permit frequent rates of reinforcer delivery, but may permit more immediate or higher quality reinforcers). For example, Reed and Martens (2008) used procedures similar to those described by Neef et al (1992Neef et al ( , 1994 with students receiving standard educational services (i.e., not special education), to demonstrate the utility of matching to academic performance. In Experiment 1 of Reed and Martens' study, the difficulty of the problems in each stack was matched to students' current instructional level (i.e., in a previous assessment, the students demonstrated the ability to complete these problems accurately and fluently).…”
Section: Figure 3 the Top Panel Depicts Possible Variations In Bias mentioning
confidence: 99%
See 1 more Smart Citation
“…Address correspondence and requests for reprints to Jay Harding, University Hospital School, Room 251, 100 Hawkins Drive, The University of Iowa, Iowa City, Iowa 52242. fects in natural settings (e.g., Mace, Neef, Shade, & Mauro, 1994;Neef, Mace, & Shade, 1993;Neef, Shade, & Miller, 1994). As discussed by Neef et al (1994), response alternatives in natural contexts are often asymmetrical across reinforcer dimensions.…”
mentioning
confidence: 99%